The Gambia in transition: Towards a new constitutional order - Nabaneh, Satang; Abebe, Adem; Sowe, Gaye (Pretoria University Law Press (PULP), 2022)
The Gambia opened a new chapter in her history after 22 years of authoritarian rule under former dictator Yahya Jammeh, heralding the promise of a 'New Gambia.' The country is at a critical juncture in its transition from Jammeh's autocratic rule to a fully-fledged democracy. The ambitious transitional processes include the Truth Reparations and Reconciliation Commission to create an official record of past abuses and crimes, the Constitutional Review Commission to draft a new Constitution, and the permanent National Human Rights Commission to build a human rights culture. The Gambia in transition: Towards a new constitutional order is a diverse collection of timely, rigorous, and insightful essays on human rights, constitutional reform, rule of law and democratic governance. It serves as an important reference for academics, policymakers, researchers, civil society organisations, human rights defenders, learners, and the public at large.